Show that \\( \Rightarrow \\) as defined in Eq. (4.6) indeed satisfies Eq. (4.5).

[Previous](https://forum.azimuthproject.org/discussion/2228)
[Next](https://forum.azimuthproject.org/discussion/2231)

\[ \tag{4.5} b \wedge c \le d \text{ iff } b \le (c \Rightarrow d) \]

\[ \tag{4.6}
\begin{array}{c c | c}
c & d & c \Rightarrow d \\\\
\hline
\text{true} & \text{true} & \text{true} \\\\
\text{true} & \text{false} & \text{false} \\\\
\text{false} & \text{true} & \text{true} \\\\
\text{false} & \text{false} & \text{true}
\end{array}
\]